Восхождение: гимнастика на Олимпиадах - Титов Юрий Евлампиевич (Советская Россия, 1978)
Экземпляры: КХ (20211022) / Инвентарный номер: 701713 / Сис.шифр: 796.4 / Авт.знак: Т 45 / ГРНТИ: 77.29.51 / ББК: 75.661